Factors determining the quality of masonry – differentiation of resistance and reliability - Zięba , Joanna; Buda-Ożóg, Lidia; Skrzypczak, Izabela (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
A house or any other building without walls is truly hard to imagine. The first thing usually associated with walls is, of course, masonry. Today, masonry walls perform a load-bearing function in buildings up to four above-ground floors, in the higher parts of the buildings they perform a protective and stiffening function. However, there is a widespread opinion that the designer does not have to check the bearing capacity of masonry structures because masonry are were stand, are standing and will stand. Not everyone, however, currently works the wall as it should. The problem is that a lot of emphasis is now placed on reducing construction times. Therefore, there are a number of factors affecting the quality of the masonry structure, which overall reduce their safety. The article presents the influence of the quality of masonry on the differentiation of bearing capacity and reliability of an example masonry structure. The analyses included various values γm of the partial factor, recommended in the national annex PN-EN 1996-1, depending on the category of masonry units, class execution of works and type of mortar. In addition, a decrease in load capacity and reliability caused by the increase of the initial eccentric resulting from the inaccuracy of the masonry wall was examined.